Anopheles culicifacies Complex: Geographical Distribution of Sibling Species and Existing Methods for Their Identification - de Silva, B.G.D.N.K. (My University, 2009)
Meaningful epidemiological studies and effective vector control programmes depend on efficient methods for differentiating among major vector, poor vector and non-vector of anopheline species complexes. Anopheles culicifacies, has a wide distribution in India, extending to Ethiopia, Yemen, Iran, Afghanistan and Pakistan in the West and Bangladesh, Myanmar, Thailand, Laos and Vietnam in the East. It is also found in Nepal and Southern China to the North and extends to Sri Lanka in the South. This species exist as a complex of five sibling species provisionally designated as A, B, C, D and E. Species A and Bare predominant in Northern and Southern part of India whereas species B is recorded all over the Indian subcontinent. Species Band E are found in Sri Lanka to date. Various methods and techniques have been used for identifying sibling species ranging from crossing experiments cytogenetics, isoenzymes, hydrocarbon profile, DNA probes, rDNA-PCR, mt DNA-PCR and RAPD-PCR. Studies of the suitability among different methods delineating the complex of An. culicifacies, the major malaria vector, mainly in the Indian subcontinent and in Sri Lanka have been discussed here.
Keywords: Anopheles culicifacies; Mosquito control